Limites objetivos da jurisdição arbitral nos contratos coligados - Monteiro, Vitor José de Mello (2017)
The present thesis aims to analyze the extension of the limits of the arbitral jurisdiction, from a objective point of view, in the related contract when only one, or just a few of them, presents an arbitral clause and the dispute arose requires the analysis not only of the this, or these, specific contracts, but also of the other contracts of this same “contractual net” that does not have an arbitral clause in it. The issue becomes relevant at the moment that the Defendant does not agree with the discussion, in the arbitration, of the contract that does not have an arbitral clause, and the arbitrator has the tough job to decide whether he has jurisdiction to scrutinize the whole dispute, including the ones related to the contract that does not have an arbitral clause. The analysis of the problem requires a deep exam of the legal regime of the related contracts and of the jurisdictional characteristic of the arbitration, in a manner that allows to stablish the premises which are important to give basis to the conclusions